Tradisi Perkawinan Masyarakat Di Desa Karelayu Kecamatan Tamalatea Kabupaten Jeneponto Dalam Perspektif Hukum Islam - Sudirman, Muh.; Mustaring, Mustaring; Hambali, Dwi Januarti (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
This study aims to determine: 1) The implementation of community marriage traditions in Karelayu Village, Tamalatea District, Jeneponto Regency in the perspective of Islamic Law, 2) Community views regarding the implementation of marriage. The research method used in this study is qualitative research methods. Data collection techniques include: observation, interviews, and documentation. The data obtained from the results of the study were processed using data analysis in a qualitative descriptive manner. The results showed that: 1) The implementation of the community marriage tradition in Karelayu Village, Tamalatea District, Jeneponto Regency was in accordance with the prevailing Islamic religious recommendations. Starting at the Mange A'boya stage to A'matoang. 2) The marriage tradition is a hereditary inheritance that has a close correlation with religion and will not be displaced by changing times.